Medication compliance among individuals with hypertension and type 2 diabetes mellitus in urban slums of amalapuram: Findings from a cross-sectional study. - Rao T, Nageswara; Ramesh, B . Naga; Dr S Suguna; Sayana, Dr Suresh Babu (Student's Journal of Health Research Africa, 2025)
Background: Medication adherence is essential for effective management of chronic conditions such as hypertension and type 2 diabetes mellitus. In urban slum populations, adherence is often hindered by socioeconomic limitations, low health literacy, and lack of awareness, contributing to poor clinical outcomes. Objective: This study aimed to evaluate the prevalence of medication adherence among individuals with hypertension and type 2 diabetes mellitus, identify associated sociodemographic and clinical factors, and explore barriers to adherence. Methods: A descriptive cross-sectional study was carried out in the urban slums of Amalapuram from January 2025 to June 2025. A total of 100 adult patients with both hypertension and type 2 diabetes were enrolled. Data regarding sociodemographic characteristics, clinical history, and treatment practices were collected using a pretested structured questionnaire. The 8-item Morisky Medication Adherence Scale (MMAS-8) was used to assess adherence levels. Descriptive statistics were applied to determine prevalence, while associations with influencing factors were explored. Results: The mean age of participants was 54.2 ± 9.6 years, with females accounting for 56%. Most patients (71%) belonged to the lower socioeconomic class. The average duration of hypertension and diabetes was 7.3 ± 3.8 years and 6.1 ± 3.2 years, respectively. Adherence assessment revealed that 28% had high adherence, while 36% each showed medium and low adherence. Younger age (<50 years), female gender, higher education, shorter disease duration, and middle socioeconomic status were positively associated with better adherence. The main reasons for poor compliance were forgetfulness (44%), discontinuation after symptomatic relief (28%), financial constraints (15%), and adverse drug reactions (8%). Conclusion: Medication adherence among patients with coexisting hypertension and diabetes in Amalapuram urban slums was suboptimal, with nearly three-fourths demonstrating medium or low compliance. Recommendations: Regular patient counseling, routine adherence assessment, and ensuring affordable access to medicines are essential to improve compliance and reduce long-term complications.